Relativismo e ceticismo na dialética serial de Proudhon - Borba, João Ribeiro de Almeida (2008)
The objective of this study is to examine how the method and the knowledge theory of Pierre-Joseph Proudhon (1808-1865), multi-disciplinar thinker and theorist-founder of the political anarchism, replays to the important philosophical problem of the construction of objective knowledges when this construction is confronted with some particular difficulties, that are imposed by contaminations due to the presence of personal approaching filters. The objective is justified by the fact whereof, although the number of studies about the proudhonian thoughs in sociology, economy and politics, the studies upon the philosophy of Proudhon, until now, are very poor. Until now, this author is almost unknown in the philosophical researches. The objective is justified, moreover, because his philosophy offers a way to establish a better dialogue and interaction among the philosophical theories and the popular thinking, applied to the social and diary-life questions. The pointed problem brings forward the discussions that Proudhon establish with known philosophies, and clearly localize, to the philosophers and academical searchers, his place in this particular area of knowledge. Focused in Proudhon s theory, the pointed problem offers, as a natural complement, a landscape of the political-philosophical confrontations at the XIXth century, about the destiny and the ways of human thinking, at the cross-roads of the alternatives offered by philosophy, religion and science. The examined hypothesis is that the way found by Proudhon to respond the focused problem, is a coherent and fruitful combination of relativism and skepticism, in an universal method to evaluate and develop knowledges. The Proudhon s theory is named by him Serial Theory , and his method, Serial Dialetics . This explanation, consequently, will show how relativism and skepticism are combined by Proudhon at the construction of this method and this theory, to offer a replay to the focused philosophical problem